Propuesta blog educativo “Mi poder” para la formación de niños resilientes de 5 años en una institución educativa Inicial, 2020 - Alayo Casas, Merilym Streixy (2022)
The present descriptive purposeful research work had the general objective of designing an educational blog "My power" for the formation of resilient children at the age of 5 in an initial education EI._x000D_ To design the pedagogical proposal My Power, a previous diagnosis was made about the levels of resilience that children of the I.E. Pilgrims of the Lord, using an assessment scale as an assessment instrument, taking into account the Autonomy, Self-Image and Empathy dimensions._x000D_ The general results analyzed showed us that in the evaluation of the resilience of 5-year-old children, the vast majority have achieved the medium level (80%) while only two children (20%) are located at the low level, justifying the necessity elaboration of the pedagogical proposal "My power".